Dependence of the mechanical properties and microstructure of ultralight magnesium‐lithium‐aluminum alloy on heat treatment conditions. Issue 3 (8th March 2021) - Mineta, T.; Kumatani, K.; Adachi, H.; Sato, H.
Abstract: Although magnesium‐lithium‐based alloys demonstrate superior workability and lower densities than conventional magnesium alloys, their mechanical properties require improvement. In this study, the effect of heat treatment conditions on the mechanical properties and microstructure of magnesium‐lithium‐aluminum alloys was investigated. Tensile tests were conducted on the alloys, and the results showed that the yield stress, ultimate tensile strength, and total elongation were significantly dependent on the heat treatment conditions. The relationship between the yield stress and grain size was not governed by the Hall‐Petch relationship. The activation volume of various heat‐treated samples estimated from the strain rate jump test was smaller for higher yield stress. Wide‐angle x‐ray scattering indicated that the second phase with a Bragg spacing of 1.7 nm was generated after heat treatment. It is found that the state of the second phase periodic structure affects the mechanical properties of the magnesium‐lithium‐aluminum alloy. Abstract : Mechanical properties and microstructure of magnesium‐lithium‐aluminum alloys subjected to various heat treatments were investigated. The samples which were heat‐treated at high temperatures had high strength. Moreover, it is found by two‐dimensional wide‐angle x‐ray scattering experiments that periodic structures of the second phase were formed.